Machine Learning Algorithms Popular Algorithms for Data Science and Machine Learning, 2nd Edition. - Bonaccorso, Giuseppe (Packt Publishing Ltd, 2018)
Machine learning explores the study and construction of algorithms that can learn from and make predictions on data. This book will act as an entry point for anyone who wants to make a career in Machine Learning. It covers algorithms like Linear regression, Logistic Regression, SVM, Naïve Bayes, K-Means, Random Forest, and Feature engineering.